The high risk of malarial recurrence in patients with Plasmodium-mixed infection after treatment with antimalarial drugs: a systematic review and meta-analysis - Aongart Mahittikorn; Frederick Ramirez Masangkay; Kwuntida Uthaisar Kotepui; Giovanni De Jesus Milanez; Manas Kotepui (Parasites & Vectors, 2021)
Abstract Background Malaria mixed infections are often unrecognized by microscopists in the hospitals, and a delay or failure to treat Plasmodium-mixed infection may lead to aggravated morbidity and increased mortality. The present study aimed to quantify the pooled proportion and risk of malarial recurrences after the treatment of Plasmodium-mixed infection. The results of the study may provide benefits in the management of Plasmodium-mixed infection in co-endemic regions. Methods This systematic review and meta-analysis searched the international Prospective Register of Systematic Reviews (PROSPERO; ID = CRD42020199709), MEDLINE, Web of Science, and Scopus for potentially relevant studies in any language published between January 1, 1936, and July 20, 2020, assessing drug efficacy in patients with Plasmodium-mixed infection. The primary outcome was the pooled prevalence of Plasmodium parasitemia after initiating antimalarial treatment for Plasmodium-mixed infection. The secondary outcome was the pooled risk ratio (RR) of malarial recurrence in Plasmodium-mixed infection compared with those in Plasmodium falciparum and Plasmodium vivax mono-infection. The pooled analyses were calculated by random-effects meta-analysis. After the initial treatment in different days of recurrences (≤ 28 days or > 28 days), the risk of Plasmodium parasitemia was compared in subgroup analysis. Results Out of 5217 screened studies, 11 were included in the meta-analysis, including 4390 patients from six countries. The pooled prevalence of all recurrences of Plasmodium-mixed parasitemia was 30% (95% confidence interval (CI) 16–43; I 2: 99.2%; 11 studies). The RR of malarial recurrence within 28 days after the initial treatment (clinical treatment failure) of Plasmodium-mixed parasitemia compared with the treatment of P. falciparum was 1.22 (p: 0.029; 95% CI 1.02–1.47; Cochran Q: 0.93; I 2: 0%; six studies), while there was no significant difference in the risk of recurrence 28 days after initial treatment compared with the treatment of P. falciparum (p: 0.696, RR: 1.14; 95% CI 0.59–2.18; Cochran Q < 0.05; I 2: 98.2%; four studies). The subgroup analysis of antimalarial drugs showed that significant malarial recurrence within 28 days was observed in patients treated with artemisinin-based combination therapies (ACTs) with no significant heterogeneity (p: 0.028, RR: 1.31; 95% CI 1.03–1.66; Cochran Q: 0.834; I 2: 0%). Conclusions The present findings showed a high prevalence of malarial recurrence after the initial treatment of Plasmodium-mixed infection. Moreover, significant malaria recurrence of mixed infection occurred within 28 days after treatment with ACTs. Graphic Abstract